Acanthocephalan infection and sparganosis in a green tree snake (Dendrelaphis punctulata). Issue 9 (September 2014) - Hill, AG; Ladds, PW; Spratt, DM
<x xml:space="preserve">Abstract</x> Acanthocephalan and spargana parasites were identified within a body wall mass during exploratory surgery in a wild green tree snake. Acanthocephalan parasites have not previously been reported in this species. Surgical excision, the treatment of choice, could not be achieved because of the extensive infiltration of the coelomic cavity.